2012
DOI: 10.1152/ajpcell.00411.2011
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of acid-base transporters by reactive oxygen species following mitochondrial fragmentation

Abstract: Mitochondrial morphology is determined by the balance between the opposing processes of fission and fusion, each of which is regulated by a distinct set of proteins. Abnormalities in mitochondrial dynamics have been associated with a variety of diseases, including neurodegenerative conditions such as Alzheimer's disease, Parkinson's disease, and dominant optic atrophy. Although the genetic determinants of fission and fusion are well recognized, less is known about the mechanism(s) whereby altered morphology co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 61 publications
(70 reference statements)
1
13
0
Order By: Relevance
“…It has been shown that mitochondria dynamically change their morphologies in response to oxidative stress [38][40]. Therefore, we tested whether the two striatal cell lines showed different pattern changes in mitochondrial morphology in response to H 2 O 2 .…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that mitochondria dynamically change their morphologies in response to oxidative stress [38][40]. Therefore, we tested whether the two striatal cell lines showed different pattern changes in mitochondrial morphology in response to H 2 O 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, these pathways are not limited to anti-aging responses. For example, mtROS signaling has also been implicated in other homeostatic pathways and processes, including wound healing (Xu and Chisholm, 2014), survival under hypoxia (Schieber and Chandel, 2014), intracellular pH homeostasis (Johnson et al, 2012), cell differentiation (Hamanaka and Chandel, 2010; Hamanaka et al, 2013; Tormos et al, 2011), and innate immunity (West et al, 2011). Accordingly, the remainder of this Review will be devoted to the role of mtROS in whole-body physiology, with the main focus on neuroendocrine control of systemic metabolism in mammals.…”
Section: Mitochondrial Ros Signaling In Organismal Physiology: Lessonmentioning
confidence: 99%
“…Thapsigargin (Abcam) (Xu et al 2001), mito-TEMPO (Sigma) (Johnson et al 2012), and cyclosporine A (Sigma) (Giacomotto et al 2013) were dissolved in DMSO and added to the NGM media (cooled to 55°) to the appropriate final concentrations, and animals were grown on these plates as previously described.…”
Section: Drug Treatmentsmentioning
confidence: 99%